Psycho-social factors influencing cervical cancer screening among female Civil Servants in Delta State, Nigeria - Beatrice Ohaeri; Priscilla U. Ebunu; Chizoma, M. Ndikom; Joel O. Aluko (African Journal of Behavioural and Scale Development Research, 2019)
This study assessed the psycho-social barriers to cervical cancer screening services utilization as well as uptake of Human Papilloma Virus (HPV) vaccination among Delta State's female civil servants. The study design is descriptive while the sampling method employed was that of multi- stage. Four hundred and thirty five (435) willing women were selected as study participants. A validated self-administered structured questionnaire of 0.7 reliability coefficient (Cronbach alpha) was used for data gathering. A total of 435 out of 437 questionnaires administered to the participants were properly completed. Thus, the response rate was 99.5%. Data analysis was performed with descriptively using frequency/percent counts and findings are presented in tables and chart. The findings indicate that, 55.4% were aware of carcinoma of cervix; 93.6% had not participated in cervical cancer screening as at the time of data collection. As much as 54.5% of the participants viewed costs of the screening test as a psychosocial factor that impedes cervical screening services use, while 58.2% reported inaccessibility. However, 73.6% indicated willingness to attempt cervical cancer screening. Cervical cancer screening is a strategy directed towards ensuring barest minimum incidence reduction in cervical cancer. Embarking on cervical cancer awareness campaign could help to increase knowledge in cervical cancer preventive measures. Besides, subsidizing cost of cancer screening is capable of lessening the financial burden, as well as improving utilization of cervical cancer screening services. Subsequently, global cervical cancer burden will be reduced, with a consequent reduction in mortality.